When care is defined by science: Exploring veterinary medicine through a more‐than‐human geography of empathy. Issue 3 (29th July 2018) - Donald, Megan Martha
Abstract : Veterinary medicine is the profession that is widely perceived as being at the forefront of animal care in the United Kingdom (UK). It is a form of care that is multi‐spatial and multi‐species: veterinary surgeons are involved in broad debates about animal welfare while also intimately caring for our pet companions. In order to regulate the profession, the Royal College of Veterinary Surgeons provides the Code of Professional Conduct (CPC) as the principal ethical framework that must be adhered to by all UK veterinary surgeons. The main aim of the CPC claims to ensure that the animal is, first and foremost, the primary consideration in veterinary medicine. By exploring the CPC in relation with animal geographies, emotional geographies and science and technology studies, this paper shows how the CPC remains anthropocentric and focused on a rational scientism that limits affective attunement with non‐human animals and distrusts the role of emotion and affect in veterinary medicine. These ethical‐spatial implications are then shown to extend beyond the CPC and into the conceptual terrain of ethics teaching in undergraduate veterinary education. As a way through this ethical tangle, a more‐than‐human geography of empathy is proposed. This notion takes the site of empathy as its geographical focus and suggests that a more critical, situated and holistic understanding of empathy might allow for a more thorough consideration of the tensions between human and animal and science and emotion in veterinary medicine and human geography more widely. Abstract : Veterinary medicine is the profession that is widely perceived as being at the forefront of animal care in the United Kingdom (UK). In order to regulate the profession, the Royal College of Veterinary Surgeons provides the Code of Professional Conduct (CPC) as the principal ethical framework which must be adhered to by all UK veterinary surgeons. By exploring the CPC in relation with animal geographies, emotional geographies and science and technology studies, this paper shows how the CPC remains anthropocentric and focused on a rational scientism which limits affective attunement with non‐human animals and distrusts the role of emotion and affect in veterinary medicine.